The Role Of Tribal Relations In The Turkish States (VII - VIII Centuries) - Behzod Makhmudov (Zien Journals, 2024)
This article deals with tribal relations in many states formed by the Turks in the early Middle Ages. It is noted that the process of constant competition with other tribes to get an important position in the state administration was an important factor for Turkic tribes to keep their own tribal interests regardless of which country they are in
Keywords: Turkic khanate; Turkic state; Qarluq; Nushibi